(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
In Bangladesh, the practice of nuclear medicine is expanding daily in both the public and private sectors. For Nuclear Medicine facilities to operate safely and effectively, strict radiation shielding is necessary to lower risks to patients, staff, and the public. This paper describes the radiation safety procedures maintained at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS), including emergency planning, waste management, monitoring systems, occupational health precautions, and shielding techniques. NINMAS manages radiation exposure using dose-tracking technologies and forefront shielding materials. With notable dose reductions seen, data from thyroid uptake and I-131 therapy procedures highlight the crucial function of shielding. I-131 dosages without shielding reached 80 mSv/h, but shielding reduced this to less than 5 mSv/h. With protective barriers, 18F-FDG doses decreased from 56 uSv/h to less than 10 uSv/h in PET-CT procedures, showing comparable advantages. To ensure regulatory compliance, NINMAS keeps careful records and complies with waste management standards. This paper highlights the way by which NINMAS has become an influential organization in the Nuclear Medicine community by playing a crucial role in developing safety standards in Bangladesh. Bangladesh J. Nuclear Med. 27(2): 234-240, 2024